Kecerdasan Spiritual sebagai Variabel Moderating pada Pengaruh Narsisme terhadap Perilaku Keputusan Investasi - M. Riduan Abdillah; Astia Putriana; Gati Anjaswari (Politeknik Ganesha Medan, 2022)
This research aimed to examine empirically the impact of narcissism on investment decision behavior with spiritual intelligence as a moderating variable. The method used in this research is quantitative. The population of this research is D3 college students of accounting program class of 2020 at Politeknik Negeri Tanah Laut as a State University (PTN) and S1 college students of accounting program class of 2019 and 2020 at Sekolah Tinggi Ilmu Ekonomi Nasional Banjarmasin as Private Universities (PTS). The samples of this research are 195 college students, obtained using the purposive sampling technique. This type of data uses primary data through distributing questionnaires to respondents while path analysis is used to test research hypotheses in order to formulate research results by means of statistical testing through SPSS software and WarpPLS. The result shows that narcissism affects investment decision behavior. This research also finds that spiritual intelligence can not moderate the effect of narcissism on investment decision behavior. These findings help to obtain insight regarding the special concern on approach that can minimize aggressive investment decision behavior which is narcissism. These empirical findings can also be used as benchmarks for similar research, especially in responding to the challenges of the times and the rise of socio-economic phenomena among millennials during the Covid-19 period for universities.